Analisis Pola asuh Orang Tua yang Menikah Dini (14-19 Tahun) Di Kecamatan Tampan Kota Pekanbaru - Ulfa Mulyani; Melani; Masril (Program Studi Bimbingan dan Konseling, FKIP Universitas Pancasakti Tegal, 2023)
It was found that underage married couples (14-19 years) had the wrong way of educating children and parenting styles that were not on target. Parents who marry at an early age have a parenting style that still ignores and neglects their rights and obligations to their children, so that it greatly impacts the child's survival. This study aims to look at the parenting style of parents who marry early (14-19 years). This research method uses descriptive qualitative research. The results of this study explained that there were found to be parenting styles of neglecting premissive parents who married at an early age. The parenting style of parents who marry early is seen from three aspects, namely psychological aspects, physical aspects and aspects of parenting knowledge. Psychologically, parents who marry early do not have maturity in raising children. From the physical aspect, parents who marry early pay less attention to the health and cleanliness of their children's bodies. Aspects of parenting science, parents who marry early are limited in understanding child care patterns so that parenting patterns occur. The research method used is descriptive qualitative research. This research was conducted from October to November 2022 which was carried out in Simpang Baru Village, Tampan District, Pekanbaru City. The subjects of this study were 4 parents aged 14 to 19 years when they were married. Direct researcher as an instrument in this study. Data collection techniques used are observation and interviews. Data is analyzed through data reduction, data display and drawing conclusions. In order for the data to be obtained properly, to ensure the validity of the data, source triangulation was carried out to re-check the correctness of the data obtained in the field.